2008
DOI: 10.1007/s10765-007-0353-1
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Investigation of Pt/Pd Thermocouples in the Framework of the Euromet Project 857

Abstract: The objective of the EUROMET Project 857 in the field of thermometry, "High-temperature fixed points for improved thermocouple calibrations," is the development of robust high-temperature fixed points based on metal-carbon eutectic alloys for the calibration of thermocouples above 1,084 • C. This paper describes the construction and investigation of Pt/Pd thermocouples to be used to compare different cobalt-carbon (Co-C) fixed-point cells constructed by the three participants of this project. A set of three Pt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…During further ageing, from 200 h to 500 h, the Pt/Pd thermocouple retained its stability within about 0.8 µV (34 mK). These data at Co-C indicated that the stability of this Pt/Pd thermocouple is likely to be comparable to those reported by Edler et al [2] in their Fig. 2.…”
Section: Stability Evaluationsupporting
confidence: 89%
See 2 more Smart Citations
“…During further ageing, from 200 h to 500 h, the Pt/Pd thermocouple retained its stability within about 0.8 µV (34 mK). These data at Co-C indicated that the stability of this Pt/Pd thermocouple is likely to be comparable to those reported by Edler et al [2] in their Fig. 2.…”
Section: Stability Evaluationsupporting
confidence: 89%
“…The thermoelements were cleaned with ethyl alcohol and distilled water. The Pd wire was annealed electrically in air for 9.5 h at approximately 1300 • C and then 0.5 h at 450 • C. The Pt wire was electrically annealed for 9 h at the same temperature, followed by 0.5 h at 750 • C and then 0.5 h at 450 • C prior to cooling to ambient temperature by switching off the current [2]. The wires were then inserted into a twin-bore re-crystallized alumina insulator tube (Al 2 O 3 , 99.7 % purity, outer diameter of 4 mm, inner diameter of 1.2 mm, length of 710 mm) which was pre-cleaned by baking at 1500 • C, in air, for 24 h. The measuring junction of the Pt/Pd thermocouple was prepared by bending the Pt arm into a U-shape, then welding the two thermoelements directly to each other [5,6].…”
Section: Pt/pd Thermocouplementioning
confidence: 99%
See 1 more Smart Citation
“…Only brief details of the Pt/Pd thermocouples developed for this project are given here as the detailed investigations and results from the participating laboratories are reported in a separate paper [17].…”
Section: Platinum/palladium Thermocouplesmentioning
confidence: 99%
“…
In my previous article [1] I discussed some of the innovations that are taking place at the National Physical Laboratory (NPL) 1 in improving high temperature measurement. Starting with the current defined temperature scale ITS-90 [2, 3], I introduced the concepts of high-temperature fixed points [4], new types of thermocouple for use to 1500°C [5,6] and developments in self-validation for contact thermometry sensors [7] and showed that high temperature measurement is undergoing a quiet revolution throughout the measurement chain. Here I want to set the work at NPL in a broader context of developments in the European Union (EU), again led from NPL, through the European Metrology Research Programme 2 project "HiTeMS: High Temperature Measurement Solutions for Industry".
…”
mentioning
confidence: 99%